MULTIMODAL APPROACH TO THE TREATMENT OF ESOPHAGEAL CANCER - U.B. URMONOV; A.YU. DOBRODEEV; S.G. AFANASYEV; A.V. AUGUSTINOVICH; E.O. RODIONOV (Паёми Сино, 2019)
Objective: To study the effectiveness and tolerability of preoperative chemotherapy (CHT) in combination with radical surgery in patients with esophageal squamous cell carcinoma (ESCC) II-III stages